A Study on the Pathways of Implementing Heritage Education in Dujiangyan from the Perspective of Heritage Education: 遗产教育视角下都江堰开展文化遗产教育的路径研究 - ZHANG Yiming; Long ZHANG; Xue WANG (Mandarinable: Journal of Chinese Studies, 2026)
As a "City of Three Heritage Inscriptions" integrating the honors of World Cultural Heritage, World Natural Heritage, and World Heritage Irrigation Structures, Dujiangyan boasts unique resources for heritage education. From the perspective of heritage education, this study systematically sorts out its core concepts and analyzes the significance of carrying out heritage education in Dujiangyan. Through investigation, it is found that issues such as insufficient systematization in education and a lack of in-depth participation mechanisms still exist although local initiatives have been actively explored in relevant fields. The study has proposed targeted optimized pathways, aiming to transform heritage education in Dujiangyan from one-way instillation to dynamic inheritance, thereby turning the world heritage site into a cultural classroom full of perception, participation and inheritance.